Proses Berpikir Mahasiswa Field Independent dan Field Dependent Dalam Memahami Konsep Grup - Gregorius Taga (UNIKA SANTU PAULUS RUTENG, 2019)
The thought process is a cognitive activity that occurs in the mind of someone who is not visible. The thought process involves some manipulation of knowledge in the cognitive system. Knowledge stored in memory is combined with new information to form new knowledge and changes in behavior in a person related to the situation at hand. A person's thought process is very dependent or related to his cognitive style. Cognitive style consists of independent field cognitive style (FI) and field dependent cognitive style (FD). Field independent cognitive style (FI), meaning that individuals tend not to be affected by manipulation of deceptive elements in the context and are able to analytically determine simple parts that are separate from the original context, whereas cognitive style dependent fields (FD) mean individuals tend to be difficult to determine a simple part of the original context or be easily influenced by the manipulation of the deceptive elements in the context because of seeing it globally. The structure of algebra as part of modern algebra is one subject that has characteristics with a strict axiomatic deductive structure. The purpose of giving algebra structure courses is a means to train students to think logically. Theoretically, children in the formal operation stage do not have much difficulty learning the algebraic structure course, including mastering the theorems of the course. However, this study does not discuss the problem of students 'difficulties in completing assignments, but is related to students' thought processes in completing assignments, namely understanding concepts. Thus, this article will examine how the thinking processes of students who have the cognitive style of FI and FD in understanding group concepts as one of the topics in the structure of algebra. Students who have an independent field cognitive style respond to an assignment tend to rely on cues from within themselves. While students who have a field dependent cognitive style see the environmental conditions as a clue in responding to a stimulus.